A Conceptual Study of Snehapana Administration and its Types Based on Karma - Nanarkar, Prasad; Mangal, Gopesh (International Research Journal of Ayurveda & Yoga, 2022)
Panchakarma is backbone of ayurvedic treatment, in which Snehana is one of the important procedures. In Ayurveda it is mentioned under the heading of Shadhvidhupkrama, which shows how Snehana is not only limited to Purvakarma of Shodhana therapy but also as a main treatment in different types of disease. Snehana therapy is administrated to a patient in two different ways, Bahya (external oleation) such as Abhyanga (therapeutic massage), Unmardana(manual massage in ascending direction), Parisheka (therapeutic streaming), Janu Basti (therapeutic retention of oil over knee region), Kati Basti therapeutic retention of oil over lumbosacral region) etc. and second one is Abhyantara, it is also called as Snehapana (internal oleation), which is divided into three varieties on the basis of their effect that is, Brimhana, Shamana and Shodhana (detoxification therapy). If Snehapana is done effectively it will give fruitful effect of Shodhana therapy, but Snehapana if not done properly, it affects Shodhana therapy and also leads to various complications. There is a hesitancy in patients for oral intake of Snehana Dravya as The present article is an attempt to highlight the effects of Snehapana with the help of classical references and mode action according to modern science.